2012
DOI: 10.1007/s13402-011-0067-z
|View full text |Cite
|
Sign up to set email alerts
|

An expression signature of phenotypic resistance to hepatocellular carcinoma identified by cross-species gene expression analysis

Abstract: Background and aims Hepatocarcinogenesis is under polygenic control. We analyzed gene expression patterns of dysplastic liver nodules (DNs) and hepatocellular carcinomas (HCCs) chemically-induced in F344 and BN rats, respectively susceptible and resistant to hepatocarcinogenesis. Methods Expression profiles were performed by microarray and validated by quantitative RT-PCR and Western blot. Results Cluster analysis revealed two distinctive gene expression patterns, the first of which included normal liver o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…Steric hindrance by the NO 2 group in the 3-position of tyrosine may prevent phosphorylation at the 4-position thereby causing dysregulation of activation/deactivation processes in the affected proteins [33, 45, 9598]. Such considerations have implications for cognitive dysfunction following low dietary vitamin D.…”
Section: Discussionmentioning
confidence: 99%
“…Steric hindrance by the NO 2 group in the 3-position of tyrosine may prevent phosphorylation at the 4-position thereby causing dysregulation of activation/deactivation processes in the affected proteins [33, 45, 9598]. Such considerations have implications for cognitive dysfunction following low dietary vitamin D.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, PTPN13 gene mutations have been identified in colorectal, head and neck, and hepatocellular carcinoma [35]. Besides, reduced PTPN13 expression in breast cancer correlates with decreased survival in patients [6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of GNMT in human HCC have shown that GNMT gene alteration , including insertion/deletion polymorphism in the promoter region, is an early event in HCC development and that GNMT could be considered a new tumor susceptibility gene for HCC [ 61 , 77 ]. In respect to these findings, it is interesting the observation that some genes involved in methionine metabolism, such as BHMT and GNMT , are connected to the genetic susceptibility to liver cancer [ 77 ].…”
Section: Gnmt In Liver Injurymentioning
confidence: 99%
“…Studies of GNMT in human HCC have shown that GNMT gene alteration , including insertion/deletion polymorphism in the promoter region, is an early event in HCC development and that GNMT could be considered a new tumor susceptibility gene for HCC [ 61 , 77 ]. In respect to these findings, it is interesting the observation that some genes involved in methionine metabolism, such as BHMT and GNMT , are connected to the genetic susceptibility to liver cancer [ 77 ]. Chemically induced hepatocarcinogenesis in genetically susceptible F344 rats is characterized by the development of numerous DN that progress to HCCs, whereas the same treatments induce in the genetically resistant BN rats only a few slow-proliferating DN and HCCs [ 77 ].…”
Section: Gnmt In Liver Injurymentioning
confidence: 99%